2021
DOI: 10.1016/j.sdentj.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood caries prevalence and associated risk factors among Saudi preschool children in Riyadh

Abstract: Aim To determine the prevalence of early childhood caries (ECC) and investigate the effect of associated risk factors on ECC prevalence in preschool children in Riyadh, Saudi Arabia. Methods This cross-sectional study included Saudi preschoolers aged 36–71 months. Parents/guardians completed a structured, self-administered questionnaire assessing sociodemographics; medical, dental, and dietary history; and oral hygiene practices. Children were orally examined for dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
4
9
0
Order By: Relevance
“…In the present study, a statistically significant associations were reported between ECC prevalence, age of start tooth brushing, tooth brushing frequency and methods and parental supervision during the tooth brushing which was in accordance with numerous other studies carried out in different countries (11,20,22,24,25,30).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, a statistically significant associations were reported between ECC prevalence, age of start tooth brushing, tooth brushing frequency and methods and parental supervision during the tooth brushing which was in accordance with numerous other studies carried out in different countries (11,20,22,24,25,30).…”
Section: Discussionsupporting
confidence: 93%
“…Results of the present study showed a statistically significant association between ECC and history of dental visits (P < 0.001) and children who visited a dentist during their infancy had a higher ECC prevalence. This is consistent with previous reports of an association between dentist visit and ECC in children (20,39). This might reflect the fact that most children see the dentist only for an existing dental problem and not for prevention or control, and that parents in Tunisia believe that children do not need to be taken to the dentist unless they have a dental problem or pain caused by a carious lesion (20).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations